Management of ankle fractures in children. (2nd April 2019) - Marson, Ben A; Craxford, Simon; Ollivere, Benjamin J
Abstract : Ankle fractures are a common injury in children and adolescents – 1 in 1000 children will sustain an ankle fracture each year. Understanding the diagnosis and management of these injuries is vital for any doctor or clinician working in the emergency department, orthopaedics or providing community care. This review identifies the important features of high- and low-risk ankle fractures, how to prevent the use of unnecessary radiation and the management of these injuries. Fractures may be at high or low risk of instability and are managed accordingly. Many can be treated with conservative management in a cast, including unstable injuries following reduction. However, particular fracture patterns associated with the tibial growth plate need careful assessment of fracture reduction with cross-sectional imaging before committing to conservative management.